Absorption and disposition of naringenin and quercetin after simultaneous administration via intestinal perfusion in mice. Issue 9 (12th August 2016) - Orrego-Lagarón, Naiara; Martínez-Huélamo, Miriam; Quifer-Rada, Paola; Lamuela-Raventos, Rosa M.; Escribano-Ferrer, Elvira
Abstract : As common constituents of vegetables, naringenin and quercetin are ingested together; for a clearer understanding of their bioavailability it is insightful to study them together. Abstract : As common constituents of tomatoes and other fruits and/or vegetables, naringenin and quercetin are usually ingested together, so for a clearer understanding of their bioavailability, metabolic fates and health benefits, it is more insightful to study them together. The purpose of the present work was to study how co-administration of naringenin and quercetin at realistic doses (3.5 μg ml −1 and 2.36 μg ml −1, respectively) influences their absorption and intestinal first-pass metabolism. A single-pass intestinal perfusion model in mice ( n = 4–6) was used. Perfusate (every 10 minutes), blood (at 60 min) and bile samples were analysed by an UPLC-ESI-MS/MS method to evaluate the presence of the aglycones and their metabolites. Both naringenin and quercetin showed high permeability coefficients when administered separately (7.71 ± 0.82 × 10 −4 cm s −1 vs. 7.30 ± 1.95 × 10 −4 cm s −1, respectively), but these values decreased by 50% with co-administration (4.09 ± 0.89 × 10 −4 cm s −1 for naringenin and 3.18 ± 0.45 × 10 −4 cm s −1 for quercetin). Moreover, the level of phase II metabolites in perfusion, plasma and bile samples increased when naringenin and quercetin were administered together. The higher biliary excretion of these metabolites could thus favour the entero-hepatic recycling of the aglycones and metabolites. The results of this study may have several useful applications: to know and consider the possible interactions between polyphenols and drugs that use the same mechanism of absorption and elimination; when polyphenol-rich nutritional supplements are supplied, and in our regular diets to optimize the health benefits afforded by the biological activities of such aglycones and/or metabolites.